2016
DOI: 10.1182/blood-2015-08-660977
|View full text |Cite
|
Sign up to set email alerts
|

Compound mutations in BCR-ABL1 are not major drivers of primary or secondary resistance to ponatinib in CP-CML patients

Abstract: Key Points Ponatinib induces durable responses regardless of baseline BCR-ABL1 mutation status in CP-CML patients. No single or compound mutant consistently confers primary or secondary resistance to ponatinib in CP-CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…Two patients who had received 42 and 45 mg daily (efCave ~26 and 28 nM) achieved durable major molecular response (MMR) in 168 and 87 days, respectively, whereas the other patient with this CM, who had received an average daily dose of 32 mg (corresponding to an efCave of ~24 nM), needed 583 days to reach MMR, and was withdrawn from the study 82 days after having achieved this. 5 The latter observation is in line with an inadequately low dose of ponatinib, but it is necessary to consider the possibility that the slow response may have been attributable to a mutation-independent mechanism.…”
mentioning
confidence: 97%
“…Two patients who had received 42 and 45 mg daily (efCave ~26 and 28 nM) achieved durable major molecular response (MMR) in 168 and 87 days, respectively, whereas the other patient with this CM, who had received an average daily dose of 32 mg (corresponding to an efCave of ~24 nM), needed 583 days to reach MMR, and was withdrawn from the study 82 days after having achieved this. 5 The latter observation is in line with an inadequately low dose of ponatinib, but it is necessary to consider the possibility that the slow response may have been attributable to a mutation-independent mechanism.…”
mentioning
confidence: 97%
“…This feature is attributed to the compound's unique structure which allows it to bind and inhibit ABL1 with no steric hindrance due to the T315I mutation. 132,133 The drug was tested in the Ponatinib Phpositive acute lymphoblastic leukemia (ALL) and CML Evaluation (PACE) phase II study in which 449 patients with CML in the chronic and advanced phases and Phpositive ALL with resistant to or intolerance from dasatinib or nilotinib or with the T315I mutation were enrolled. The patients received once daily 45 mg ponatinib, and the results indicated that the drug had considerable activity in all patients, including those in advanced phase disease, regardless of base-line kinase domain mutations and the responses seemed to be durable.…”
mentioning
confidence: 99%
“…To determine the extent of false compound mutations in our sequencing assay, we mixed cDNA from patients with only one mutation (Y253H+E255K; Y253H+T315I; E255K+T315I). The recombination rate (calculated as previously described by Deininger et al 29 ) was on average 17% per 100 bp (data not shown).…”
Section: Additional Tki Resistance Mutationsmentioning
confidence: 99%
“…In future studies, the generation of chimeric reads could be reduced by modified sequencing strategies (single molecule consensus sequencing) 28 or could be mathematically corrected. 29 However, the aforementioned advances are not sufficient to resolve the clonal evolution of cases with cytogenetic aberrations in addition to the initial Philadelphia chromosome, e.g. duplication of the Philadelphia chromosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation